2D Materials Boost Advanced Zn Anodes: Principles, Advances, and Challenges - Zheng, Songhe; Zhao, Wanyu; Chen, Jianping; Zhao, Xiaoli; Pan, Zhenghui; Yang, Xiaowei (Nano-Micro Letters, 2023)
Aqueous zinc-ion battery (ZIB) featuring with high safety, low cost, environmentally friendly, and high energy density is one of the most promising systems for large-scale energy storage application. Despite extensive research progress made in developing high-performance cathodes, the Zn anode issues, such as Zn dendrites, corrosion, and hydrogen evolution, have been observed to shorten ZIB’s lifespan seriously, thus restricting their practical application. Engineering advanced Zn anodes based on two-dimensional (2D) materials are widely investigated to address these issues. With atomic thickness, 2D materials possess ultrahigh specific surface area, much exposed active sites, superior mechanical strength and flexibility, and unique electrical properties, which confirm to be a promising alternative anode material for ZIBs. This review aims to boost rational design strategies of 2D materials for practical application of ZIB by combining the fundamental principle and research progress. Firstly, the fundamental principles of 2D materials against the drawbacks of Zn anode are introduced. Then, the designed strategies of several typical 2D materials for stable Zn anodes are comprehensively summarized. Finally, perspectives on the future development of advanced Zn anodes by taking advantage of these unique properties of 2D materials are proposed. Highlights: 1 The mechanisms of two-dimensional (2D) materials protecting Zn anodes were summarized. 2 The recent progress of 2D materials boosting advanced Zn anodes was exhaustively categorized and reviewed. 3 The prospects in the commercial application of aqueous zinc ion batteries were discussed.